ANALISIS CAKUPAN PEMERIKSAAN IVA TEST DAN PAP SMEAR PADA PASANGAN USIA SUBUR - Rahmawati Mading; Siti Saleha; Cipta Pramana (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
The Inspection Visual Acetic acid (IVA) and Pap smear tests in Benteng sub-district are still lacking and very minimal. This study aims to find out how the scope of the IVA test and Pap smear examinations for couples of childbearing ages in Benteng Kepulauan Selayar District in 2021. The type of research used is descriptive analytic with a cross-sectional research design by making couples of childbearing ages as the research sample. The target in the Benteng Health Center area with non-probability sampling technique and accident sampling technique, totaling 93 people. The research used univariate data analysis with frequency distribution tables, bivariate analysis with chi-square technique. The results of the bivariate analysis showed that there was a significant relationship between age and the IVA and Pap smear tests (p = 0.029), there was no significant relationship between education and the IVA and Pap Smear tests (p = 0.049), there was a significant relationship between knowledge and the tests. IVA and Pap Smear (p = 0.027), there was a significant relationship between attitudes with the VIA and Pap Smear tests (p = 0.020), and there was a significant relationship between husband's support with the VIA and Pap Smear tests (p = 0.017). The conclusion of this research is from the coverage analysis that greatly affects the success of the IVA test and pap smear examination, it is the husband’s involvement or husband’s support.